Power Flow Study for UTP Microgrid - Roslan, Muhamad Fazril (Universiti Teknologi PETRONAS, 2016)
Power flow is an important tool used for planning, to determine the best operation for a power system and exchange of power between utility companies. The power flow study in a UTP Microgrid (a group of interconnected loads and distributed energy resources within the grid) constitutes a study of paramount importance. The study reveals the electrical performance and power flows (real and reactive) for specified condition when the system is operating under steady state. This research is conducted to make a simulated model to study on how power flow in UTP microgrid network. From the findings obtained, it may give an alternative to monitor power flow using Power World Simulator Software.